Thrombectomy in Extensive Stroke May Not Be Beneficial and Is Associated With Increased Risk for Hemorrhage. Issue 10 (2nd September 2021) - Meyer, Lukas; Bechstein, Matthias; Bester, Maxim; Hanning, Uta; Brekenfeld, Caspar; Flottmann, Fabian; Kniep, Helge; van Horn, Noel; Deb-Chatterji, Milani; Thomalla, Götz; Sporns, Peter; Yeo, Leonard Leong-Litt; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: This study evaluates the benefit of endovascular treatment (EVT) for patients with extensive baseline stroke compared with best medical treatment. Methods: This retrospective, multicenter study compares EVT and best medical treatment for computed tomography (CT)–based selection of patients with extensive baseline infarcts (Alberta Stroke Program Early CT Score ≤5) attributed to anterior circulation stroke. Patients were selected from the German Stroke Registry and 3 tertiary stroke centers. Primary functional end points were rates of good (modified Rankin Scale score of ≤3) and very poor outcome (modified Rankin Scale score of ≥5) at 90 days. Secondary safety end point was the occurrence of symptomatic intracerebral hemorrhage. Angiographic outcome was evaluated with the modified Thrombolysis in Cerebral Infarction Scale. Results: After 1:1 pair matching, a total of 248 patients were compared by treatment arm. Good functional outcome was observed in 27.4% in the EVT group, and in 25% in the best medical treatment group ( P =0.665). Advanced age (adjusted odds ratio, 1.08 [95% CI, 1.05–1.10], P <0.001) and symptomatic intracerebral hemorrhage (adjusted odds ratio, 6.35 [95% CI, 2.08–19.35], P <0.001) were independently associated with very poor outcome. Mortality (43.5% versus 28.9%, P =0.025) and symptomatic intracerebral hemorrhage (16.1% versus 5.6%, P =0.008) were significantly higher in the EVT group. The lowest rates of good functional outcome (≈15%) were observed in groups of failed and partial recanalization (modified Thrombolysis in Cerebral Infarction Scale score of 0/1–2a), whereas patients with complete recanalization (modified Thrombolysis in Cerebral Infarction Scale score of 3) with recanalization attempts ≤2 benefitted the most (modified Rankin Scale score of ≤3:42.3%, P =0.074) compared with best medical treatment. Conclusions: In daily clinical practice, EVT for CT–based selected patients with low Alberta Stroke Program Early CT Score anterior circulation stroke may not be beneficial and is associated with increased risk for hemorrhage and mortality, especially in the elderly. However, first- or second-pass complete recanalization seems to reveal a clinical benefit of EVT highlighting the vulnerability of the low Alberta Stroke Program Early CT Score subgroup. REGISTRATION: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT03356392.